Markedly Elevated Carbamazepine-10,11-epoxide/Carbamazepine Ratio in a Fatal Carbamazepine Ingestion - Jason L. Russell; Henry A. Spiller; Daniel D. Baker (Case Reports in Medicine)
Carbamazepine is a widely used anticonvulsant. Its metabolite, carbamazepine-10,11-epoxide, has been found to display similar anticonvulsant and neurotoxic properties. While the ratio of parent to metabolite concentration varies significantly, at therapeutic doses the epoxide concentration is generally about 20% of the parent. We report a case of fatal carbamazepine overdose in which the epoxide metabolite concentration was found to be 450% higher than the parent compound, suggesting a potential role for metabolite quantification in severe toxicity.